Public–Private Partnerships in Ecotourism Development in Protected Areas: A Case Study of Tunkinsky National Park in Russia - MAKSANOVA, Lyudmila; IVANOVA, Sembrika; BUDAEVA, Darima; ANDREEVA, Alyona (Journal of Environmental Management and Tourism, 2020)
This paper discusses the opportunities offered by public–private partnerships in developing ecotourism infrastructure in protected areas. The paper also addresses the issues contributing to threats and conflicts while implementing infrastructure projects. In order to fulfil research objectives, the authors employ a sociological instrument. Using a snowball method, the authors selected 34 experts with professional competencies in tourism development, natural resource management, protected area management, and public-private partnerships. The results of this study demonstrate a potential demand for the mechanisms of public-private partnerships when developing ecotourism infrastructure. Using the case study of Tunkinsky National Park, the authors identified potential threats and conflicts in the process of preparation and delivery of public-private partnership projects for ecotourism infrastructure development.